An Approach to the Efficient Syntheses of Chiral Phosphino‐ Carboxylic Acid Esters. Issue 14 (16th October 2015) - Chew, Renta Jonathan; Sepp, Kristel; Li, Bin‐Bin; Li, Yongxin; Zhu, Peng‐Cheng; Tan, Nguan Soon; Leung, Pak‐Hing
Abstract: The catalytic hydrophosphination reaction is one of the most sustainable chemical transformations today. Here, the palladium‐catalyzed asymmetric PH addition of diarylphosphines with N ‐enoylbenzotriazoles and analogues is described. Chiral phosphine products are obtained in 100% atom economy and without cumbersome protection–deprotection manipulations. The obtained products can be subsequently transformed to bear various functionalities, including phosphino‐carboxylic esters which play critical roles in catalysis and as synthetic aids. Anti‐tumour activities of the corresponding gold‐phosphine complexes have been explored, contributing to existing chemotherapeutic research in cancer treatment. Abstract :